Carbohydrate-Based Polymers For Cartilage Regeneration (Journal of Pharmaceutical Negative Results, 2023)
This paper intends to accomplish the following objectives: The goals of this review are threefold: The goals of this review are threefold: first, to evaluate the current state of cartilage substitution and regeneration; second, to analyse the patented biomaterials currently used in preclinical and clinical stages; and third, to investigate the potential of polymeric hydrogels for some of these applications and the factors that hamper their clinical success. Hydrogels are a biomaterial that has been the subject of several studies and is of particular interest for this inquiry. Here's what each of these two groups looks like: First, there's the use of cellular-free biomaterials, and second, there's the use of cellular-filled biomaterials. Below, we also cover the methods of preparation and the final hydrogel characteristics. Recent approaches to enhance these materials by combining many distinct polymers in a process known as hybridization are also analysed and discussed in this article. The ideas here are quite novel. scaffolds (cellular solids), matrices (based on hydrogels), growth factors, as well as mechanical stimulation are all required for tissue formation, cartilage regeneration, and therapeutic use. It's possible that a combination of cellular solid scaffolds, hydrogel-based matrices, growth factors, and mechanical stimulation will accomplish this. This is crucial in order to optimise the quality of the critical materials to attain the best possible performance. The most interesting and potentially useful materials for this purpose are polymer mixtures and hybrids. The formation of cartilage-like tissue with biomimetic characteristics might potentially enhance the amount of cell proliferation and local tissue integration achieved by hybrid scaffolds.